(untitled) - Henle, Faye (Garden City, New York, 1965)
People often try managing their money apart from God's plan. Bad plan. Until people have an attitude change about money, it will continue to control and confuse them. How to Manage Your Money is an excellent tool to get readers on track toward a liberated financial life. This newly re-packaged bestseller contains updated material, plus a step-by-step, in-depth study of God's principles for money management.
Keywords: Finance, pesonal,Investments